Registro y administración de la violencia: usos de la desaparición de personas en México - Camilo Vicente; Carlos Dorantes (Nuevo mundo - Mundos Nuevos, 2018)
In this article we intend to describe and analyse the ways in which the disappearance of persons is recorded at two points in the recent past – counter-insurgency and the "war on drugs" – under the following hypothesis: the logics of the political administration of violence are made explicit through the forms of registration. Registration is not external to the exercise of violence, but part of it. It is not the same disappearances, nor the same context and the author of the disappearances has diversified. However, at both times, the state records of disappearances and the findings of human remains in mass graves share similar practices: the blurring of concepts and diffuse registration and the lack of certainty in the figures articulate a political purpose of social control that seeks to separate the state from responsibility. The lack of certainty about what happened, which characterizes enforced disappearances and disappearances committed by individuals, extends to the way in which the State documents them. Knowing the mechanisms of recording violence and its narrative effects is a first step in building other forms of documentation that have memory and non-repetition effects.